Espiritualidade terapêutica: critérios da logoterapia aplicados na Lectio Divina para reabilitação de adictos - Paula, Darlei de (2012)
The challenge of our time we have faced about drug abuse increases the supply of care and admissions in therapeutic communities for the rehabilitation of people affected by this disease. According to current Brazilian legislation on mental health, therapeutic settings should provide a spiritual moment in their care programs. The Roman Catholic Church has the Pastoral da Sobriedade, a department that deals with the issue of supporting the rehabilitation of addicts. Most of pastoral agents are dedicated to the task of support these therapeutic communities. However, not all of pastoral agents have clear indications of how they should work to get success at rehabilitation. Our thesis aims to answer the question: how is possible to provide a spiritual moment according to the Lectio Divina in compliance to therapeutic criteria that causes the spiritual moment as a therapeutic moment at same time? In view of this question we investigate the Logotherapy as a psychotherapeutic approach that respects the person noological sphere. In particular way, we find elements of Bibliotherapy that is one of the Logotherapy techniques has similarities Lectio Divina in its implementation as groundwork to therapeutic criteria.